The Effect of Knisley Learning Model on the Ability to Understand Mathematical Concepts in Terms of Numeration Literacy in Middle School Students - Indah Badi'ah; Aan Subhan Pamungkas; Isna Rafianti (Wilangan: Jurnal Inovasi dan Riset Pendidikan Matematika, 2020)
This research is motivated by the importance of the ability to understand mathematical concepts as one of the goals of mathematics learning and numeracy literacy as the application of concepts in solving mathematical problems. Knisley's learning model is believed to be able to improve the ability to understand mathematical concepts so that students are expected to be able to use numeracy literacy well. So the purpose of this study was to determine the effect of Knisley's learning model on the ability to understand mathematical concepts in terms of student numeracy literacy. This research was carried out at Serang MTs 1 2019/2020 school year with samples taken purposively namely class VIII A as an experimental class totaling 24 students and class VIII B as a control class totaling 24 students. The research method used is a combination method (mixed method) with concurrent embedded design. The instruments used in this study were in the form of tests of mathematical concept understanding ability, observation sheets, interview guidelines, documentation, and researchers. The results of the study concluded that increasing the ability to understand mathematical concepts of experimental class students was better than control class students. In terms of numeracy literacy, the experimental class students have good numeracy literacy in completing test of understanding mathematical concepts.